Pemberdayaan Santri melalui Pengembangan Model Pelatihan Pembuatan Parfum sebagai Media Edukasi Entrepreneurship - Umi Rossy Mardhiyah; Efvysien Nur Hasan; Ahmad Ainur Risky (Journal of Innovation and Contribution to Community Service, 2025)
The method of training and mentoring in perfume making as a form of entrepreneurship education plays a significant role in equipping students with practical skills and an entrepreneurial spirit. This program aims to provide applicable and market-relevant knowledge, giving students greater opportunities to create job opportunities after completing their education at the pesantren. The implementation of this program was carried out at Pondok Pesantren Modern 4 Bahasa Al Muhibbin, Jatirogo, Tuban. The training process began with preparation through observation and coordination, followed by the identification of students' needs and interests. The training material was then developed, covering the basics of perfume making, raw materials, mixing techniques, and marketing. The training was conducted with a combination of theory and practice, where students were allowed to directly create perfumes. The evaluation results showed an increase in students' knowledge and skills in perfume making, as well as a boost in their confidence to start small businesses. Despite challenges in production facilities, the program proved effective in enhancing students' skills and broadening their understanding of business opportunities. Moving forward, further development is needed with adequate facilities and collaboration with external parties to strengthen students' businesses.